Regulasi Potongan Ongkir Tanpa Konfirmasi Seller: Analisis Fatwa DSN-MUI No. 117/2018 pada Kasus Shopee - Putra, Ardiansyah; Hasanah, Uswatun (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2025)
This study aims to examine the policy of automatic shipping fee deductions and service charges implemented by the Shopee e-commerce platform from the perspective of Islamic economic law, specifically referring to Fatwa DSN-MUI No. 117/DSN-MUI/II/2018 on Information Technology-Based Financing Services in accordance with Sharia principles. The findings indicate that, as of July 1, 2024, Shopee unilaterally enrolled all sellers into the Free Shipping XTRA program, accompanied by automatic service fee deductions without explicit consent from the sellers. This practice raises concerns over violations of fundamental principles of Islamic contracts, including mutual consent, clarity of contract terms, and transparency of information. In several cases, sellers have experienced financial losses due to unabsorbed shipping discrepancies and unexpected service charges. Based on contemporary Islamic commercial jurisprudence and the objectives of Islamic law, such a policy may be categorized as a coerced contract, containing elements of excessive unfair pricing and deliberate ambiguity. These contradict key Sharia principles of justice, public benefit, and wealth protection, as stated in Qur’anic verses such as Surah An-Nisa [4]:29 and Al-Baqarah [2]:188, which are among the foundations of DSN-MUI fatwas. This study recommends a policy reform that includes explicit digital consent mechanisms, transparent fee disclosures, and the provision of opt-out rights for sellers, to ensure valid contracts and balance in technology-based commerce.